2004
DOI: 10.1074/jbc.m306673200
|View full text |Cite
|
Sign up to set email alerts
|

Glycodelin A, Not Glycodelin S, Is Apoptotically Active

Abstract: Glycodelin, previously known as PP14 (placental protein-14), is a kernel lipocalin secreted by the glandular epithelium of the endometrium upon progesterone stimulation and by the seminal vesicles. The isoform of the protein present in female reproductive tissue, glycodelin A (GdA), and the male counterpart, glycodelin S (GdS), have identical amino acid sequences, but strikingly different N-linked glycans. It is well documented in literature that GdA is an immunosuppressive protein, and we have shown that this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…High fucosylation and no sialylation (13) on GdS perhaps keep this region inaccessible. This hypothesis is supported by our observations that full-length glycodelin expressed in P. pastoris is inactive where there is a high level of glycosylation and a lack of sialylation (16,26).…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…High fucosylation and no sialylation (13) on GdS perhaps keep this region inaccessible. This hypothesis is supported by our observations that full-length glycodelin expressed in P. pastoris is inactive where there is a high level of glycosylation and a lack of sialylation (16,26).…”
Section: Discussionsupporting
confidence: 67%
“…Another function of GdA well documented in the literature is immunosuppression (3) and induction of apoptosis in T cells (4). Recent studies from our laboratory demonstrated clearly that GdS lacks apoptotic activity as well (26). It was therefore logical to determine whether the glycans on GdA also dictate its immunosuppressive characteristics.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations